DIAGNOSIS OF BREAST CANCER: SOCIO-ECONOMIC, CLINICAL, REPRODUCTIVE AND BEHAVIORAL PROFILE OF THE WOMEN - Franciéle Marabotti Costa Leite; Cintya Raquel Araújo Gonçalves; Maria Helena Costa Amorim; Susana Bubach (Universidade Federal do Paraná, 2012)
A descriptive study with a quantitative approach, whose objective was to outline the socio-economic, clinical, behavioral and reproductive profile of the women of the town of São Mateus - in the state of Espírito Santo who were living through the diagnosis of breast cancer in the period from 2005 to 2010. 23 women were interviewed, between January and April 2011. Approximately 70% were in the age range 36 to 49 and ≥ 60; 60,9% were married or cohabiting; 47.8% had not finished their primary education and 39,2% belonged to class D; 26,1% had a family history of mammary neoplasm and 78,2% had discovered the cancer through self-examination; 52,2% had undergone non-conservative surgery; 87% had already been pregnant and 60% had their first pregnancy between 20 and 29 years of age; 78,3% carried out self-examinations and 87% the mammography. The study allowed the identification of needs and behaviors which may be changed.